Impact of a short postgraduate course in rational pharmacotherapy for general practitioners - AKICI, AHMET; KARAALP, ATİLA (WILEY, 2004)
Aims The impact of a short postgraduate course on rational pharmacotherapy planning behaviour of general practitioners (GP) was investigated via a face-to-face interview with 25 GPs working at health centres in Istanbul. Methods GPs were randomly allocated to control and intervention groups. Intervention group attended a 3-day-training program preceded and followed by a written exam to plan treatment for simulated cases with a selected indication. The participants' therapeutic competence was also tested at the post-test for an unexposed indication to show the transfer effect of the course. In addition, patients treated by these GP's were interviewed and the prescriptions were analysed regarding rational use of drugs (RUD) principles at the baseline, 2 weeks and 4 months after the course. Results At the baseline there was not any significant difference between the control and intervention groups in terms of irrational prescribing habits. The questionnaires revealed that the GPs were not applying RUD rules in making their treatment plans and they were not educating their patients efficiently. Training produced a significant improvement in prescribing habits of the intervention group, which was preserved for 4 months after the course. However, very low scores of the pretest indicate the urgent necessity for solutions. Conclusions Training medical doctors on RUD not only at the under- but also at the postgraduate level deserves attention and should be considered by all sides of the problem including academia, health authorities and medical associations.
Keywords: PRESENTING CLINICAL-PHARMACOLOGY; POLYPHARMACY; IMPROVE; ASTHMA; INTERVENTION; THERAPEUTICS; EDUCATION; SODIUM; DRUGS